Model Komunikasi Melalui Media Sosial Dalam Mengatasi Radikalisasi Pemahaman Agama Di Kalangan Remaja - Moh Sakir; Talitha Carlen Amora; Hamida Syari Harahap (Mathematics Education Study Program, 2025)
Studying more deeply about the communication model through social media in overcoming radicalism in understanding religion among teenagers is important. Considering that teenagers are the driving force and the future of the nation, studying the communication model through social media in overcoming radicalism in understanding religion among teenagers can produce input in preventing radicalism since adolescence. This study is a literature review sourced from secondary sources, namely books and journals that discuss major themes, namely; communication, social media, religious radicalism and its implications in society. The communication process involves sharing information, ideas, or attitudes. Therefore, communication requires three basic elements: source, message, and destination (recipient). From an Islamic normative perspective, Ayish states that the concept of communication in the Arab-Islamic tradition can be explained through four dichotomous themes, namely individualism-conformity, transcendentalism-existentialism, rationality-intuition, and hierarchy-egalitarianism. This concept is different from the communication model in Western theory which is universal Keywords: Communication, Social media, Religious radicalism; Teenagers